Advancing Workplace Mediation Through Integration of Theory and Practice - Bollen, Katalien; Euwema, Martin; Munduate, Lourdes (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book compares the unique features of workplace mediation to other contexts of mediation, as well as the specific competences each situation requires of the mediator. It covers many important issues related to workplace mediation and discusses interventions by managers, such as conflict coaching and informal mediation. It proposes a new model to assess the effectiveness of mediation, and discusses the impact of legal systems, HRM policies, as well as power structures, and cultural differences. The book takes into account perspectives from multiple disciplines, such as management, business, psychology, law and sociology. It also discusses mediation aspects from a variety of cultural and regional contexts. The book advances knowledge about the application, process and effects of workplace mediation and includes practical tips for scholars, practitioners, mediators and managers to enhance their mediation practice or to foster constructive conflict management in organizations.
Introduction.-Bollen, Euwema and Munduate;A situated model of effective mediation -- Coleman, Kugler, Mazzaro and Chatman;Workplace mediation based on the underlying structure of conflict -- Kals, Thiel and Freund;Workplace mediation: Lessons from negotiation theory.-Höhne, Loschelder, Gutenbrunner and Majer;Workplace mediation: A multi-party and multi-issue view.-Stimec;Mediating workplace disputes: Confronting facts and emotions.-Herrman;Multiple ways of working through it: Integrating conflict coaching and workplace mediation.-Brinkert;Conflict coaching and workplace mediation: Issues and recommendations for intelligent dispute system design (in USA).-Jones;The role of workplace mediation and conflict management systems in organisations: A developing country perspective (South Africa).-Jordaan and De Wulf;HRM practices and workplace mediation in the UK.-Deakin;Cultural differences in workplace mediation -- Cea, Ramirez and Medina;Manager as mediator? Mediator as manager! Tips for managers and team leaders for the effective use of conflict and dispute resolution at the workplace -- Butts;A psychological toolbox for managers and mediators: An update of best practice instruments -- Harnack;Mediation within and between teams -- Tjosvold;E-mediation at work -- Parlamis and Ebner;Discussion -- Bollen, Euwema and Munduate.
Keywords: Applied psychology; Personnel management